Essential Medicines Availability and Affordability ; A case study of the Top Ten Registered Diseases in Builsa District - NYANWURA, E.M (University of Ghana, 2010)
Access to essential medicines is a major component for an effective health service delivery system. The purpose of this study was to evaluate the availability and affordability of essential medicines used in the treatment of the top ten registered diseases in Builsa District in the year 2009.
Keywords: ESSENTIAL MEDICINES; AVAILABILITY; AFFORDABILITY; DISEASES; BUILSA DISTRICT